P121 Speech And Language Therapy In Pulmonary Rehabilitation: The Implication Of Education Sessions On Dysphagia Management. (10th November 2014) - Lillie, SF; Haines, J; Vyas, A; Fowler, SJ
Abstract : Introduction: Pulmonary rehabilitation (PR) programs use multidisciplinary teams to optimise physical and social functioning of patients with chronic respiratory impairment. Such patients demonstrate an increased prevalence of oropharyngeal dysphagia as a consequence of impaired co-ordination between respiration and swallowing function. Often patients will not be aware of the warning signs of dysphagia and unfortunately will not be seen by a speech and language therapist until they are admitted to hospital. We report the outcomes of a pilot scheme whereby such patients underwent education, assessment and treatment for dysphagia as part of their PR programme.. Methods: The pilot scheme ran between June 2013 and May 2014. Intervention consisted of: (1) a one hour group education session on the signs, symptoms and risks of dysphagia; (2) screening for oropharyngeal dysphagia; and (3) individual outpatient management in Airways Clinic. The majority of patients attending the education sessions had a diagnosis of Chronic Obstructive Pulmonary Disease (COPD). Results: The education programme was delivered to 72 patients, and resulted in a significant improvement in dysphagia knowledge. The average score pre education was 3/11 and post education was 8/11. Fourteen patients (19%) exhibited or reported symptoms of dysphagia. Of these two patients were overtly aspirating and required food/fluid modification and seven patient's required instrumental assessment in the form of fibre endoscopic evaluation of swallowing (FEES). During FEES, three patients showed penetration of food/ fluids and were at risk of silent aspiration. These patients attended for further SLT where diet/ fluids were modified, posture was assessed and dysphagia therapy was introduced. Conclusions: Dysphagia education and management of patients in PR can contribute the early identification, patient awareness and self-management of dysphagia. We have confirmed that undiagnosed but clinically important dysphagia is present in patients undergoing PR. We are investigating whether improved dysphagia knowledge and early identification of dysphagia symptoms leads to reduced exacerbations and improved quality of life.